Implementation of Non-Pharmacological Therapy by Giving Melon Fruit (Cucumis Melo L) to Patients with Hypertension - Asep Gunawan; Dedi Supriadi; Alfi Fadilah (LPPM STIKes Muhammadiyah Ciamis, 2023)
Objective: This case study is to implement non-pharmacological therapy by administering melon fruit to reducing blood pressure in hypertensive patients. Method: This study uses descriptive analysis with a case study approach. This case study is to describe, objectively describe, and explore in-depth data regarding nursing care for hypertensive patients with ineffective family management problems in the Health UPTD Work Area of the Cikoneng Health Center. When conducting research, the authors also make observations at certain times in the form of assessments, nursing diagnoses, interventions, implementation, and evaluation. Providing non-pharmacological therapy to eat melons to reduce high blood pressure and respondents' adherence to eating melons The observation began after being given health education, which aimed to find out whether there was adherence to eating melons and whether there was a change in blood pressure or no change. This study was conducted on Mrs. C with hypertension in Colendra Hamlet, RT.13 RW.05, Sindangsari Village, Cikoneng District, Ciamis Regency, in the working area of the UPTD Cikoneng Health Center from March 31 to April 3, 2023, for 4 days of visit. Result Based on the results of an assessment of hypertensive family members and there were nursing diagnoses assigned to the family, namely ineffective family health management, related to the inability of the family to care for sick family members and the inability of the family to make the right decisions. Given the intervention and implementation of non-pharmacological therapy of melon fruit to reduce the patient's blood pressure. The implementation was given for 3 days, the patient's blood pressure gradually decreased from 160/100 MmHg to 150/90 MmHg, but had not yet reached normal levels. So that the action of giving melon fruit can be continued and applied in daily life independently. Conclusion: Giving non-pharmacological therapy giving melon fruit has proven to be useful for lowering blood pressure in hypertensive patients, the benefits of therapy will be maximized if done regularly and gradually.